Factors Influencing Repeat Visit Intention with Brand Image as an Intervening Variable at G Hospital - Sinthya Dhewi; Wahyuni Dian Purwati; Intan Silviana (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The rapid growth of hospitals has intensified competition in the hospital business, making it increasingly challenging. This situation necessitates the need to ensure that patients return to the same hospital, in other words, the need to enhance repeat visitation interest, which has a significant impact on the hospital's business sustainability. This research was conducted due to a significant decrease in the number of outpatient visits at Gandaria Hospital. The study aims to analyze the influencing factors on repeat visitation interest at Gandaria Hospital, with repeat visitation interest as the dependent variable, word of mouth, and social media as independent variables, and brand image as an intervening variable. This research employs a quantitative approach with data analysis techniques, specifically descriptive analysis using Excel & SPSS software and Path Analysis using AMOS software. The sample size, calculated according to Hair's formula, consists of 75 outpatient patients. The results of hypothesis testing indicate that word of mouth and social media have a significant positive impact on repeat visitation interest. Social media has a greater influence compared to word of mouth on repeat visitation interest. The brand image variable is proven to be an intervening variable between word of mouth and repeat visitation interest but not between social media and repeat visitation interest.